Lincoln's way : how six great Presidents created American power - Striner, Richard, 1950- (Lanham, Md. : Rowman & Littlefield Publishers, 2010)
Credits Abraham Lincoln, Theodore Roosevelt, Franklin D. Roosevelt, Harry S. Truman, Dwight D. Eisenhower, and John F. Kennedy with increasing the power of the United States.
Forgotten paths in American politics -- From the founders to Abraham Lincoln -- From Lincoln to Theodore Roosevelt -- The legacy crosses party lines : from Theodore to Franklin D. Roosevelt -- The legacy as great power statecraft : from Truman to Nixon -- The legacy in ruins : from Carter to George W. Bush -- Horizons.
Includes bibliographical references (p. 249-289) and index.
Keywords: Presidents -- United States -- History; Political leadership -- United States -- History; Federal government -- United States -- History; Power (Social sciences) -- United States -- History; United States -- Politics and government; Lincoln, Abraham, -- 1809-1865 -- Influence